2021
DOI: 10.3390/land10020137
|View full text |Cite
|
Sign up to set email alerts
|

Assessing CO2 Emissions from Passenger Transport with the Mixed-Use Development Model in Shenzhen International Low-Carbon City

Abstract: Assessing transport CO2 emissions is important in the development of low-carbon strategies, but studies based on mixed land use are rare. This study assessed CO2 emissions from passenger transport in traffic analysis zones (TAZs) at the community level, based on a combination of the mixed-use development model and the vehicle emission calculation model. Based on mixed land use and transport accessibility, the mixed-use development model was adopted to estimate travel demand, including travel modes and distance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Therefore, the research should consider the crucial function of electric investment and its focus on CO 2 emissions. The multi-use, multi-occupational land design is necessary to reduce transportation CO 2 emissions [ 42 ] Additionally, more challenging local ecological parameters also help to lower CO 2 emissions. Ecological parameters' direct influence coefficient has an inversely significant value [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the research should consider the crucial function of electric investment and its focus on CO 2 emissions. The multi-use, multi-occupational land design is necessary to reduce transportation CO 2 emissions [ 42 ] Additionally, more challenging local ecological parameters also help to lower CO 2 emissions. Ecological parameters' direct influence coefficient has an inversely significant value [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the idea is to study the opposite data, where tourist arrivals are a dependent variable instead of previous research where tourist arrivals were treated as an independent variable [108]. Overall, this variable escalated as a calculated bump in this research, while trending researchers found determinants, i.e., island travel, crisis or commuting, affecting carbon footprint [109][110][111]. In the EU 2030 climate and energy strategy, there are three main objectives: (1) to reduce greenhouse gas emissions by 40% (compared to 1990), (2) to increase the share of renewable energy by 32% and (3) to improve energy efficiency by 32.5%, which counts towards the overall 40% emissions reduction target [112].…”
Section: Introductionmentioning
confidence: 88%
“…When it comes to mixed land use, it is considered to be an important means to solve problems such as inefficient land use and traffic jams [15], which are the main carbon emission sources in the cities. Tan et al further confirmed that mixed land use can reduce carbon emissions per capita by reducing commuting [37]. Meanwhile, when farmland and forest land are mixed, their proportion also affects carbon emissions [38].…”
Section: Land Use Mixed Land Use and Carbon Emissionsmentioning
confidence: 96%